Dinamika Penelitian Desentralisasi dan Demokrasi di Indonesia: Analisis Bibliometrik dari Tahun 1999-2025 - Selvia Junita Praja (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Decentralisation and democracy are two interrelated concepts in governance reform, particularly in improving the effectiveness of regional development. Decentralisation is often seen as an instrument to strengthen democracy by bringing the decision-making process closer to the people. This study aims to analyse the trend of research publications on decentralisation in Indonesia using a bibliometric analysis approach. The articles used in this study were obtained from Scopus data. From 472 articles found in the scopus database between 1999 and 2025. The selected articles were then managed using biblioshiny and Vosviewer software. The results show that publications related to decentralisation have fluctuated over the last 27 years. The article with the most citations entitled Decentralisation and Democracy in Indonesia: A Critique of Neo-Institutionalist Perspectives has 213 citations. Meanwhile, the highest affiliation shows that the University of Indonesia is the institution with a total of 25 publications. The mapping of articles based on the relationship between keywords (co-occurance) is formed into 8 clusters, each cluster describes topics that are often discussed in decentralisation-related literature such as Indonesia, decentralization, democracy, local government, governance approach, election, Asia and southeast Asia.